Diets, dominance hierarchies, and kleptoparasitism drive asymmetrical interactions between wolves and cougars - Wesley Binder; Joel S. Ruprecht; Jack Rabe; Matthew C. Metz; Rebecca Hutchinson; Daniel R. Stahler; Taal Levi (Proceedings of the National Academy of Sciences, 2026)
After widespread extirpation, conservation efforts have restored large carnivores to portions of their former range. Substantial research has since focused on their ability to alter ecological communities through effects on herbivores and mesocarnivores, but the principles governing competition among multiple apex carnivores remain unclear. While mesocarnivore scavenging of apex carnivore kills drive “enemies with benefits” dynamics, subordinate apex carnivores seldom rely on scavenging. Instead, they proficiently hunt prey themselves that dominant apex carnivores can steal, fundamentally altering the dynamics of their interactions. We used 9 y of contemporaneous GPS telemetry and 3,929 potential kill site investigations from a reconstituted community of sympatric wolves and cougars in Yellowstone National Park to test whether such apex–apex dynamics instead follow an “enemies without benefits” framework. Wolf movement and resource selection were strongly linked to cougar kills, resulting in carcass theft (i.e., kleptoparasitism) that drove their interactions and led to cougar mortalities. In contrast, cougars avoided wolf kills, were tied to escape terrain, and did not kill wolves, producing an asymmetric dynamic that persisted across distinct seasonal contexts. However, as elk (the shared primary prey) declined longitudinally, cougars shifted their diets to smaller-bodied deer that were kleptoparasitized by wolves at one-sixth the rate of elk kills. Our findings demonstrate that prey diversity and landscape structure are critical for subordinate apex carnivores who experience severe interference competition from their dominant counterparts. This dynamic extends trophic theory and provides a framework for predicting the coexistence outcomes of carnivore restoration and the ongoing recolonization of wolves.